Evangelicalism and fundamentalism in the United Kingdom during the twentieth century - Bebbington, D.; Jones, David Ceri (Oxford Oxford University Press, 2014)
This volume takes a detailed look at the history of Christian fundamentalism in the United Kingdom during the 20th century examining the inter-relation between fundamentalism and evangelical theology. Using detailed empirical evidence the authors challenge generalisations and enable a more nuanced understanding of the roots of fundamentalism today.
Keywords: Evangelicalism -- Great Britain -- History, 20th century; Fundamentalism -- Great Britain -- History, 20th century; Aufsatzsammlung